Military Deployment and Its Consequences for Families 2013
DOI: 10.1007/978-1-4614-8712-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of Post-Deployment Reintegration

Abstract: Although researchers have examined the 6-12 month period after which service members return home from an overseas deployment, their studies often focus on members' mental and physical health (e.g., whether or not the member is displaying symptoms of post-traumatic stress disorder or a minor traumatic brain injury). In this chapter, we take a different approach to the post-deployment reintegration period, focusing instead on the positive and negative experiences and perceptions associated with three domains tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…On the one hand, individuals may experience negative emotions such as fear, loss, powerlessness, and worry; whereas on the other hand, they may experience periods of increased self-confidence and self-discovery (Davis et al, 2011). Supporting this idea, studies have found negative and positive reintegration experiences to be orthogonal—returning service members may report both positive reintegration and negative reintegration (McCreary et al, 2014). Thus, we focus on both positive (e.g., experiences of personal growth) and negative (e.g., experiences of personal difficulties and struggles) aspects of personal reintegration postdeployment.…”
Section: Postdeployment Personal Reintegration Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, individuals may experience negative emotions such as fear, loss, powerlessness, and worry; whereas on the other hand, they may experience periods of increased self-confidence and self-discovery (Davis et al, 2011). Supporting this idea, studies have found negative and positive reintegration experiences to be orthogonal—returning service members may report both positive reintegration and negative reintegration (McCreary et al, 2014). Thus, we focus on both positive (e.g., experiences of personal growth) and negative (e.g., experiences of personal difficulties and struggles) aspects of personal reintegration postdeployment.…”
Section: Postdeployment Personal Reintegration Experiencesmentioning
confidence: 99%
“…Reintegration is broadly defined as the period of time when individuals transition back into previous personal, organizational, and social roles after a period of deployment (Currie, Day, & Kelloway, 2011). The reintegration process can have profound effects on the returning service members and family members (McCreary, Peach, Blais, & Fikretoglu, 2014). The present study focuses on personal reintegration, which refers to how an individual personally readjusts after deployment (e.g., how one begins to “feel like oneself again” after a deployment).…”
Section: Postdeployment Personal Reintegration Experiencesmentioning
confidence: 99%
“…For over a century, I-O psychologists have made major contributions to the recruitment, selection, and placement of military recruits (e.g., Lindsay, n.d.). Presently, there exists a large and growing demand for professional work psychologists to refocus their expertise on improving the lives of the hundreds of thousands of working-age men and women who exit the military each year (OCJC, 2014) and seek employment in civilian organizations that may be wary of hiring them (e.g., Kukla, Rattray, Salyers, 2015) and vary widely in appropriate responsiveness to their particular strengths and challenges (e.g., McCreary, Peach, Blais, & Fikretoglu, 2014). To this end, within the field of OHP there is also an emerging consensus that psychological problems need not reach full clinical criteria to still have detrimental effects on interpersonal and occupational functioning (e.g., Adler et al, 2011;Breslau, Lucia, & Davis, 2004).…”
Section: List Of Tablesmentioning
confidence: 99%
“…Five decades of studies show that, on average, at least two-thirds of U.S. veterans reintegrate successfully (e.g., Fulton et al, 2015;Hoge et al, 2006;IOM, 2013) and many easily transfer marketable knowledge, skills, abilities and other characteristics (KSOs) acquired through certain military occupational specialties (e.g., flywheel mechanic, meteorologist, combat surgeon) directly to gainful civilian employment (De Groat & Crowley, 2013). Nevertheless, only recently has serious scientific inquiry into the phenomena of civilian work reintegration with military populations (e.g., Brady & Hammer, 2013;McCreary et al, 2014) offered theories and critiques to explain how the reintegration process unfolds, especially for the large minority of former military personnel who consistently experience significant difficulty adapting to the civilian labor market while a majority of their fellow war comrades appear to thrive (e.g., Bonanno et al, 2012;Kulka et al, 1990).…”
Section: Key Concepts Of Proposed Studymentioning
confidence: 99%
See 1 more Smart Citation